Clustering of Various Agricultural Processors for Identifying Training Need to Promote Value Chain Development - Shruti , J. P. Sharma , R. R. Burman , R. Gills , M. Singh; A. Bhowmik (Indian Journal of Extension Education, 2018)
Considering the importance of training for capacity building of small and medium processor the study was undertaken to identify the perceived training need of various processors in different agricultural commodities. From nine selected agricultural commodities, 15 processors were selected from each commodity, constituting 135 sample sizes. The hierarchical agglomerative clustering was used to cluster these processors based on similarity for training need. It was found that the guava, mango, tomato and potato processors form cluster 2 as they required similar type of training due to comparatively less favourable supporting entrepreneurial environment as well as they obtained highest scores for training need. The third cluster included the Mushroom, Maize, Wheat and Soybean processors, which were having similar training need due to favourable supporting entrepreneurial environment as well as they obtained lower training need scores. According to Kendalls’ coefficient, all the processors were agreed that marketing (3.78) was most preferred area of training followed by technical (3.22), information (2) and social responsibility (1). The highest training need score was obtained for potato processor (2272) and lowest for soybean processor (1953).